TREASURE BASED GAME STRATEGY INNOVATION IN LEARNING ISLAMIC RELIGIOUS EDUCATION - Kiky Sakhi Amalia; Achmad Yusuf; Askhabul Kirom; Rizky Dwi Ratna (Fakultas Tarbiyah, Universitas Ibrahimy, 2024)
This research was motivated by the minimal use of fun learning models in honing students' critical thinking skills and solving problems as an effort to improve PAI learning outcomes at Kedungcangkring Elementary School. The solution to this problem is the use of the treasure based game learning model. This research aims to determine the effect of using the treasure based game model on students' learning outcomes. This type of research is R & D (Research and Develop) research with a 4D development model, this model includes define, design, develop and disseminate. Based on the analysis of evaluation test scores, there was an increase in students' cognitive learning outcomes. The resulting product aims to increase student learning motivation. Thus it can be concluded that the use of the treasure based game learning model can improve student learning outcomes. Based on data obtained from expert lecturers as a whole about treasure-based game strategies, a score of 95% was obtained. While the results of game trials in large groups with research subjects of 5 groups with an average score of 87 are categorized as successful, the results of the treasure-based strategy are feasible to be used in learning at school.